2008
DOI: 10.3844/ajabssp.2008.689.698
|View full text |Cite
|
Sign up to set email alerts
|

Distillation and Microdiffusion Modifications for total Nh4f Quantification and 15N Recovery

Abstract: Applying 15 N techniques to accurately determine the fate of fixed ammonium (NH 4f) in the strongly and weakly held pools require modifications to existing methodologies. Modifications are necessary for measurement of total NH 4f in soils by direct digestion with 5 M HF: 1 M HCl, excluding alkali pretreatment, followed by distillation and quantification of NH 4. Quantification by distillation was used as a precursor to optimize microdiffusion protocols for continuous flow-isotope ratio mass spectrometry (CF-IR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
(24 reference statements)
0
6
0
Order By: Relevance
“…1) in order to measure the concentration of total fixed NH 4 + directly (Matsuoka and Moritsuka 2011). This modification is expected to minimize the possible artifacts caused by the indirect determination of total fixed NH 4 + using separate samples (Eudoxie and Gouveia 2008), in which the concentration of exchangeable NH 4 + is subtracted from that of NH 4 + extracted by HF-HCl. To extract exchangeable NH 4 + , we added 10.0 mL of 2 mol L −1 KCl to 2.00 g of soil in a 50-mL centrifuge tube.…”
Section: Determination Of Exchangeable Nh 4 +mentioning
confidence: 99%
“…1) in order to measure the concentration of total fixed NH 4 + directly (Matsuoka and Moritsuka 2011). This modification is expected to minimize the possible artifacts caused by the indirect determination of total fixed NH 4 + using separate samples (Eudoxie and Gouveia 2008), in which the concentration of exchangeable NH 4 + is subtracted from that of NH 4 + extracted by HF-HCl. To extract exchangeable NH 4 + , we added 10.0 mL of 2 mol L −1 KCl to 2.00 g of soil in a 50-mL centrifuge tube.…”
Section: Determination Of Exchangeable Nh 4 +mentioning
confidence: 99%
“…In the preliminary experiment, grinding of the original soil was found to increase the concentration of nonexchangeable K (a cumulative value from step 2 to steps 3-5) from An experimental procedure to determine total and strongly fixed NH 4 + and the capacity of interlayer sites. Weakly fixed NH 4 + was calculated by subtraction of strongly fixed NH 4 + measured by Silva and Bremner (1966) from total fixed NH 4 + measured by Eudoxie and Gouveia (2008).…”
Section: Determination Of Exchangeable Nh 4 + and K-saturation Treatmmentioning
confidence: 99%
“…After the acid digestion, the supernatant was obtained by centrifugation and stored in a refrigerator for no longer than 2 days. The supernatant (7 mL) was steam distilled for 3 min with 4.55 mL of 10 mol L −1 potassium hydroxide (KOH) and 18.2 mL of distilled water (equivalent to 32.5 mL of 2 mol L −1 KOH per 10 mL of supernatant in the original method) to minimize recovery of alkali labile organic nitrogen during the distillation, because Eudoxie and Gouveia (2008) reported that minimal amounts of organic N from spikes were recovered after approximately 3 min of distillation at this KOH concentration (less than 0.2 percent of added N), whereas more than 97 percent of the spiked NH 4 + was recovered. The amount of NH 4 + liberated during the distillation (total fixed NH 4 + ) was measured by the indophenol method.…”
Section: Determinations Of Weakly Fixed Nh 4 + and Strongly Fixed Nh 4 +mentioning
confidence: 99%
See 2 more Smart Citations